PERSPEKTIF HADIS TENTANG IHTIKAR - Junaid bin Junaid (Institut Agama Islam Negeri Bone, 2020)
AbstractIn Islamic teaching have some problematic for some people or human being. Specially in the law of Islamic economic study, one foundation of the reference or basicly is from the hadith of the Prophet Muhammad Pbuh. Because the hadith it self contains many things which is directly related to the Islamic economics. One of the theory is about hoarding. Where the hoarding of goods based on the perspective of hadith have a bad impact and also forbidden to do. As has been forbidden by the holy prophet through his hadith.Kata Kunci: Perspektif; hadis; ekonomi Islam; Ihtikar.